Seizures induce obstructive apnea in DBA/2J audiogenic seizure‐prone mice: Lifesaving impact of tracheal implants. (16th January 2020) - Irizarry, Rachel; Sukato, Daniel; Kollmar, Richard; Schild, Samuel; Silverman, Joshua; Sundaram, Krishnamurthi; Stephenson, Stacy; Stewart, Mark
Abstract: The mechanism(s) for sudden death in epilepsy (SUDEP) remain(s) unknown, but seizure spread to brainstem areas serving autonomic and respiratory function is critical. In a rat model, we established a mechanism for SUDEP that involves seizure‐induced laryngospasm and obstructive apnea lasting until respiratory arrest. We hypothesized that DBA/2J mice, which display lethal audiogenic seizures, would be protected from death by implanting a tracheal T‐tube as a surrogate airway. In a 2 × 2 design, mice were implanted with either open or closed tracheal T‐tubes and treated with either low‐dose ketamine/xylazine to moderate thoracic spasm during the tonic seizure phase or no drug. Animals receiving both treatments had the highest survival rate, followed by animals receiving the open tube without ketamine/xylazine. The odds ratio for survival was >20 higher with an open T‐tube (odds ratio = 24.14). The impact of open tracheal tubes indicates that the mechanism of death in DBA/2J mice involves seizure‐induced upper airway obstruction until respiratory arrest. These results, our rat work, and our demonstration of inspiratory effort‐based electromyographic signals and electrocardiographic abnormalities in rats and humans suggest that seizure‐induced laryngospasm and obstructive apnea directly link seizure activity to respiratory arrest in these sudden death examples.